Debating childfree: The contestation of “childfree” discourses in Instagram - Mashita Phitaloka Fandia Purwaningtyas; Alma Alysha Br Tarigan; Jasmine Rizky El Yasinta (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
Among Indonesian netizens, the debate around “childfree” issue has become a topic of discussion in the Instagram, especially since this issue was raised by influencer Gita Savitri. Instagram netizens' opinions are divided; some support the childfree concept, but many disagree. The debate regarding childfree has even given rise to discourse polarization between narratives that are pro and anti toward childfree. This research attempts to capture and dismantle discourse contestations related to the issue of childfree on Instagram. This research was conducted with feminist critical discourse analysis method. In this research, it was found that there were three focuses of debate between the pro-childfree and anti-childfree narratives. First, the religious perspective in viewing childfree. Second, motivation to have children. Third, women’s agency in choosing not to have children. The contestation of this discourse is motivated by patriarchal and capitalist understandings which are deeply rooted and internalized in Indonesian society in general, making it difficult for them to accept views that are different from the general views which they believe to be true.